A lithium ion battery and its preparation method and electrical equipment
Through the dual electrolyte system and secondary injection technology, thin and stable SEI and CEI films are formed, which solves the problem of insufficient low-temperature performance of lithium-ion batteries, improves capacity retention rate and discharge average voltage, and shortens the optimization research cycle.
Patent Information
- Application Number
- CN202311627836.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-11-29
AI Technical Summary
The capacity retention rate and the average discharge voltage of high-nickel ternary material lithium-ion batteries during cyclic charging and discharging at low temperatures are low. The existing optimization methods have a long cycle, so methods to shorten the improvement cycle need to be developed.
Using a dual electrolyte system, the first electrolyte and the second electrolyte both contain lithium salts, impedance reducing agents, infiltration improvers and low viscosity solvents. The mass fraction of lithium salts and low viscosity solvents in the second electrolyte is higher than that of the first electrolyte. The sum of the mass fractions of the liquid, impedance reducing agent, infiltration improver and negative electrode SEI film improver is also higher than that of the first electrolyte. A thin and stable SEI and CEI films are formed through secondary injection technology to reduce the lithium ion diffusion impedance.
It significantly improves the low-temperature discharge performance of lithium-ion batteries, including improving the low-temperature capacity retention rate and discharge average voltage, and greatly shortens the battery optimization research cycle.
Smart Images

Figure BDA0004581294080000111 
Figure BDA0004581294080000121 
Figure BDA0004581294080000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion battery and a preparation method and electrical equipment thereof. Background Art
[0002] High-nickel ternary materials (lithium nickel cobalt manganese (aluminum) oxide, in which the molar amount of nickel accounts for more than 0.8 of the total molar amount of the three elements of nickel, cobalt, manganese (aluminum)) have shortcomings such as low capacity retention and low average discharge voltage during cyclic charge and discharge at low temperatures, such as -20°C. At present, the above problems are mainly solved by optimizing the formula, particle size and compaction density of positive and negative electrode materials and the formula of electrolyte, but these methods have a relatively long optimization research cycle. Therefore, it is necessary to develop a method with a relatively short improvement cycle to solve the above technical problems. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present invention is to provide a lithium ion battery and a preparation method and electrical equipment thereof, so as to improve the low temperature capacity retention rate and discharge voltage of the lithium ion battery while shortening the improvement cycle.
[0004] In a first aspect, the present invention provides a lithium ion battery, comprising an electrolyte, wherein the electrolyte comprises a first electrolyte and a second electrolyte;
[0005] The first electrolyte and the second electrolyte both include a lithium salt, a resistance reducing agent, a wettability improving agent, a negative electrode SEI film improving agent and a low-viscosity solvent, wherein the viscosity of the low-viscosity solvent in the first electrolyte and the second electrolyte at 25° C. is lower than 2.5 mPa, S and the dielectric constant is greater than 2.5;
[0006] The mass fractions of the lithium salt and the low-viscosity solvent in the second electrolyte are respectively higher than their mass fractions in the first electrolyte;
[0007] The sum of the mass fractions of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent in the second electrolyte is higher than the sum of their mass fractions in the first electrolyte.
[0008] Furthermore, the lithium-ion battery also includes a negative electrode active material, which includes a silicon material; in the first electrolyte, the mass fraction of the low viscosity solvent / the mass fraction of the silicon material in the negative electrode active material is 4.2-4.7, the mass fraction of the lithium salt is 11%-15%, and the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver is 1.5%-4.0%; in the second electrolyte, the mass fraction of the low viscosity solvent / the mass fraction of the silicon material in the negative electrode active material is 4.9-5.4, the mass fraction of the lithium salt is 12%-17%, and the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver is 2.0%-5.0%.
[0009] Furthermore, the silicon material includes at least one of silicon monoxide, silicon alloy, and silicon composite material.
[0010] Furthermore, the mass fraction of the impedance reducing agent in the second electrolyte is not lower than the mass fraction of the impedance reducing agent in the first electrolyte.
[0011] Furthermore, the mass fraction of the wettability improving agent in the second electrolyte is not lower than the mass fraction of the wettability improving agent in the first electrolyte.
[0012] Furthermore, the mass fraction of the negative electrode SEI film improver in the second electrolyte is not lower than the mass fraction of the negative electrode SEI film improver in the first electrolyte.
[0013] Furthermore, the low-viscosity solvents in the first electrolyte and the second electrolyte both include propylene carbonate and ethyl methyl carbonate; in the first electrolyte, the mass fraction of propylene carbonate is 5% to 10%, and the mass fraction of ethyl methyl carbonate is 15% to 35%; in the second electrolyte, the mass fraction of propylene carbonate is 10% to 15%, and the mass fraction of ethyl methyl carbonate is 20% to 40%.
[0014] Furthermore, at least one of the following conditions is met:
[0015] (1) The mass fraction of the first electrolyte in the electrolyte is 45% to 85%, and the mass fraction of the second electrolyte in the electrolyte is 15% to 55%;
[0016] (2) In the first electrolyte and the second electrolyte, the mass fraction of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent is 0.5% to 3%;
[0017] (3) The impedance reducing agent in the first electrolyte and the second electrolyte includes at least one of lithium difluorophosphate, lithium difluorooxyphosphate, tris(trimethylsilyl)phosphate, and tris(trimethylsilyl)borate;
[0018] (4) The wetting improving agent in the first electrolyte and the second electrolyte both includes at least one of fluorobenzene, ethyl propionate, and propyl acetate;
[0019] (5) The negative electrode SEI film improver in the first electrolyte and the second electrolyte includes at least one of vinyl sulfite, 1,4-butane sultone, propylene sulfite, dimethyl sulfite, diethyl sulfite, etc.;
[0020] (6) The lithium salt in the first electrolyte and the second electrolyte includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium perchlorate, and lithium difluorophosphate;
[0021] (7) The lithium-ion battery also includes a positive electrode, the positive electrode includes a positive electrode active material, and the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, wherein the molar amount of nickel element in the lithium nickel cobalt manganese oxide / the total molar amount of nickel element, cobalt element and manganese element is ≥ 0.8; and the molar amount of nickel element in the lithium nickel cobalt aluminum oxide / the total molar amount of nickel element, cobalt element and aluminum element is ≥ 0.8.
[0022] In a second aspect, the present invention provides a method for preparing the lithium-ion battery, comprising the following steps: injecting a first electrolyte into the dry cell for the first time, infiltrating, forming, aging, injecting a second electrolyte into the dry cell for the second time, returning helium to insert nails, welding sealing sheets, dividing the capacity, and obtaining a lithium-ion battery.
[0023] In a third aspect, the present invention further provides an electrical device, comprising the lithium ion battery or the lithium ion battery prepared by the preparation method.
[0024] Compared with the prior art, the beneficial effect of the present application is that the present application forms a thin and stable SEI film at the negative electrode and a thin and stable CEI film at the positive electrode by controlling the mass fractions of the lithium salt and the low-viscosity solvent in the second electrolyte to be higher than their mass fractions in the first electrolyte, respectively, and the sum of the mass fractions of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent in the second electrolyte to be higher than the sum of their mass fractions in the first electrolyte, thereby reducing the impedance of the diffusion of lithium ions in the negative electrode SEI film and the positive electrode CEI film, and reducing the impedance of the diffusion of lithium ions between the positive and negative electrodes, thereby improving the low-temperature discharge performance of the lithium-ion battery, such as improving the capacity retention rate and the average discharge voltage during low-temperature discharge, and greatly shortening the battery optimization research cycle. DETAILED DESCRIPTION
[0025] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0026] In this application, "low temperature" refers to below -10°C, such as -10°C, -20°C, -30°C, -50°C, etc.
[0027] According to a first aspect of the present application, there is provided a lithium ion battery, comprising an electrolyte, wherein the electrolyte comprises a first electrolyte and a second electrolyte;
[0028] The first electrolyte and the second electrolyte both include a lithium salt, a resistance reducing agent, a wettability improving agent, a negative electrode SEI film improving agent and a low-viscosity solvent, wherein the low-viscosity solvents in the first electrolyte and the second electrolyte have a viscosity at 25° C. lower than 2.5 mPa, S and a dielectric constant greater than 2.5;
[0029] The mass fractions of the lithium salt and the low-viscosity solvent in the second electrolyte are respectively higher than their mass fractions in the first electrolyte;
[0030] The sum of the mass fractions of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent in the second electrolyte is higher than the sum of their mass fractions in the first electrolyte.
[0031] The present application controls the mass fractions of lithium salt and low viscosity solvent in the second electrolyte to be higher than their mass fractions in the first electrolyte, respectively, and the sum of the mass fractions of impedance reducing agent, wettability improving agent and negative electrode SEI film improving agent in the second electrolyte to be higher than the sum of their mass fractions in the first electrolyte, so as to form a thin and stable SEI film at the negative electrode and a thin and stable CEI film at the positive electrode, thereby reducing the impedance of lithium ion diffusion in the negative electrode SEI film and the positive electrode CEI film, and reducing the impedance of lithium ion diffusion between the positive and negative electrodes, thereby improving the low-temperature discharge performance of lithium-ion batteries, such as improving the capacity retention rate and the average discharge voltage during low-temperature discharge.
[0032] The present application utilizes secondary liquid injection technology, and by controlling the first electrolyte and the second electrolyte to meet the above conditions, it can effectively improve the low-temperature discharge performance of lithium-ion batteries, improve their capacity retention rate and average discharge voltage during low-temperature discharge, and significantly shorten the battery optimization research cycle.
[0033] The lithium-ion battery also includes a negative electrode active material. The selection of the negative electrode active material is not specifically limited, such as at least one selected from silicon materials, carbon materials, alloy negative electrodes, etc., but the selection of the negative electrode active material is not limited thereto.
[0034] When the negative electrode active material includes silicon material, the low-temperature discharge performance of the lithium-ion battery is also related to the ratio of the mass fraction of the low-viscosity solvent in the first electrolyte and the second electrolyte / the mass fraction of the silicon material in the negative electrode active material, the mass fraction of the lithium salt, and the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver. Among them, the ratio of the mass fraction of the low-viscosity solvent in the first electrolyte and the second electrolyte / the mass fraction of the silicon material in the negative electrode active material will affect the thickness of the film formed on the surface of the positive and negative electrodes and the diffusion rate of lithium ions; the mass fraction of the lithium salt in the second electrolyte is controlled to be higher than the mass fraction of the lithium salt in the first electrolyte to make up for the active lithium lost in the film formation and improve the conductivity; the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the second electrolyte is controlled to be higher than the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the first electrolyte to improve the kinetics of the negative electrode and the diffusion rate of lithium ions. Preferably, in the first electrolyte, the mass fraction of the low viscosity solvent / the mass fraction of the silicon material in the negative electrode active material is controlled to be 4.2 to 4.7 (such as 4.2, 4.3, 4.5, 4.7 or a range formed by any two of the above values), the mass fraction of the lithium salt is 11% to 15% (such as 11%, 12%, 13%, 14%, 15 or a range formed by any two of the above values), and the sum of the mass fractions of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent is 1.5% to 4.0% (such as 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or a range formed by any two of the above values); in the second electrolyte, the mass fraction of the low viscosity solvent / the negative electrode active material The mass fraction of the silicon material is 4.9-5.4 (such as 4.9, 5, 5.2, 5.4 or a range formed by any two of the above values), the mass fraction of the lithium salt is 12%-17% (such as 12%, 13%, 14%, 15%, 16%, 17% or a range formed by any two of the above values), and the sum of the mass fractions of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent is 2.0%-5.0% (such as 2.0%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5.0% or a range formed by any two of the above values), so that the low-temperature discharge performance of the lithium-ion battery is better, such as the capacity retention rate and the average discharge voltage during low-temperature discharge are higher.
[0035] In some embodiments, (mass fraction of low viscosity solvent in the second electrolyte / mass fraction of silicon material in the negative electrode active material)-(mass fraction of low viscosity solvent in the first electrolyte / mass fraction of silicon material in the negative electrode active material)≥0.5, such as 0.5, 0.7, 1.0, 1.3, 1.5, 1.7 or a range formed by any two of the above values, so that the low temperature discharge performance of the lithium ion battery is better, such as the capacity retention rate and the average discharge voltage during low temperature discharge are higher.
[0036] In some embodiments, the mass fraction of the lithium salt in the second electrolyte minus the mass fraction of the lithium salt in the first electrolyte is ≥ 1%, such as 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0% or a range formed by any two of the above values, so that the low-temperature discharge performance of the lithium-ion battery is better, such as the capacity retention rate and the average discharge voltage during low-temperature discharge are higher.
[0037] In some embodiments, (the sum of the mass fractions of the impedance reducing agent, the wetting improving agent and the negative electrode SEI film improving agent in the second electrolyte)-(the sum of the mass fractions of the impedance reducing agent, the wetting improving agent and the negative electrode SEI film improving agent in the first electrolyte) ≥ 0.3%, such as 0.3%, 0.5%, 0.7%, 0.9% or a range formed by any two of the above values, so that the low-temperature discharge performance of the lithium-ion battery is better, such as the capacity retention rate and the average discharge voltage during low-temperature discharge are higher. The silicon material in the active material of the negative electrode can be selected to include at least one of silicon oxide, silicon alloy, silicon composite material, etc., wherein the silicon alloy contains silicon and at least one metal, such as the metal in the silicon alloy can be selected from Ag, Sn, Zr, Mn, Ni, Fe, Ca, Ce, La, Cr, Al, Co, Sb, Bi, As, Ge, Pb, Zn, Cd, In, Ti, Ga, etc.; the silicon composite material includes at least one of silicon-carbon composite material, etc. However, the selection of silicon material in the active material of the negative electrode is not limited to this.
[0038] In order to further improve the low-temperature discharge performance of lithium-ion batteries, and to increase the capacity retention rate and the average discharge voltage during low-temperature discharge, in some embodiments, the mass fraction of the impedance-reducing agent in the second electrolyte is controlled to be not less than the mass fraction of the impedance-reducing agent in the first electrolyte. That is, the mass fraction of the impedance-reducing agent in the second electrolyte may be the same as the mass fraction of the impedance-reducing agent in the first electrolyte, or may be higher than the mass fraction of the impedance-reducing agent in the first electrolyte.
[0039] In order to further improve the low-temperature discharge performance of lithium-ion batteries, and to increase the capacity retention rate and the average discharge voltage during low-temperature discharge, in some embodiments, the mass fraction of the wetting improver in the second electrolyte is controlled to be no less than the mass fraction of the wetting improver in the first electrolyte. That is, the mass fraction of the wetting improver in the second electrolyte may be the same as the mass fraction of the wetting improver in the first electrolyte, or may be higher than the mass fraction of the wetting improver in the first electrolyte.
[0040] In order to further improve the low-temperature discharge performance of lithium-ion batteries, and to increase the capacity retention rate and the average discharge voltage during low-temperature discharge, in some embodiments, the mass fraction of the negative electrode SEI film improver in the second electrolyte is controlled to be no less than the mass fraction of the negative electrode SEI film improver in the first electrolyte. That is, the mass fraction of the negative electrode SEI film improver in the second electrolyte may be the same as the mass fraction of the negative electrode SEI film improver in the first electrolyte, or may be higher than the mass fraction of the negative electrode SEI film improver in the first electrolyte.
[0041] The low viscosity solvent must simultaneously satisfy the viscosity at 25°C being lower than 2.5 mPa·S and the dielectric constant at 25°C being greater than 2.5. In some embodiments, the viscosity of the low viscosity solvent at 25°C is 2.4 mPa·S, 2.0 mPa·S, 1.6 mPa·S, 1.2 mPa·S, 0.8 mPa·S or a range formed by any two of the above values. In some embodiments, the dielectric constant of the low viscosity solvent at 25°C is 2.6, 3, 3.5, 4, 5, 6, 10, 20, 30, 40, 50, 60, 70, 80, 90 or a range formed by any two of the above values. The viscosity can be measured by the following test method: viscometer, rotor No. 0, 50 rpm; the dielectric constant can be measured by the following test method: cylindrical capacitor measurement method.
[0042] There is no specific limitation on the types of low-viscosity solvents in the first electrolyte and the second electrolyte. For example, both of them may include at least one of propylene carbonate (PC) and ethyl methyl carbonate (EMC), but the invention is not limited thereto. In some embodiments, in the first electrolyte, the mass fraction of propylene carbonate is 5% to 10% (such as 5%, 6%, 7%, 8%, 9%, 10% or any two of the above values formed in the range), and the mass fraction of ethyl methyl carbonate is 15% to 35% (such as 15%, 20%, 25%, 30%, 35% or any two of the above values formed in the range); in the second electrolyte, the mass fraction of propylene carbonate is 10% to 15% (such as 10%, 11%, 12%, 13%, 14%, 15% or any two of the above values formed in the range), and the mass fraction of ethyl methyl carbonate is 20% to 40% (such as 20%, 25%, 30%, 35%, 40% or any two of the above values formed in the range), so as to further improve the capacity retention rate and the average discharge voltage of the battery during low-temperature discharge. It should be noted that the types of low-viscosity solvents in the first electrolyte and the second electrolyte can be the same or different. However, the difference is usually only partial, and the mass of the low-viscosity solvent in the second electrolyte that is different from that in the first electrolyte is usually controlled within 20% of the total mass of the low-viscosity solvent in the second electrolyte (such as 20%, 15%, 10%, 5%, 1%, 0.5% or a range formed by any two of the above values).
[0043] In some embodiments, the mass fraction of the first electrolyte in the electrolyte is 45% to 85% (such as 45%, 50%, 60%, 70%, 75%, 80%, 85% or a range formed by any two of the above values), and the mass fraction of the second electrolyte in the electrolyte is 15% to 55% (such as 15%, 20%, 30%, 40%, 50%, 55% or a range formed by any two of the above values).
[0044] In some embodiments, the mass fraction of the impedance reducing agent in the first electrolyte is in the range of 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range formed by any two of the above values, so as to obtain better impedance reducing effect at a lower cost.
[0045] In some embodiments, the mass fraction of the wetting improver in the first electrolyte is generally in the range of 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range formed by any two of the above values, so as to obtain better wetting improvement effect at a lower cost.
[0046] In some embodiments, the mass fraction of the negative electrode SEI film improver in the first electrolyte is generally in the range of 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range formed by any two of the above values, so as to obtain better negative electrode film forming effect at a lower cost.
[0047] In some embodiments, the mass fraction of the impedance reducing agent in the second electrolyte is in the range of 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range formed by any two of the above values, so as to obtain better impedance reducing effect at a lower cost.
[0048] In some embodiments, the mass fraction of the wetting improver in the second electrolyte is generally in the range of 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range formed by any two of the above values, so as to obtain better wetting improvement effect at a lower cost.
[0049] In some embodiments, the mass fraction of the negative electrode SEI film improver in the second electrolyte is generally in the range of 0.5% to 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range formed by any two of the above values, so as to obtain better negative electrode film forming effect at a lower cost.
[0050] There is no specific restriction on the types of impedance reducing agents in the first electrolyte and the second electrolyte. For example, they can be selected to include at least one of lithium difluorophosphate (LiPO2F2), lithium difluorooxyphosphate, tris(trimethylsilyl) phosphate, and tris(trimethylsilyl) borate, but are not limited to this. The types of impedance reducing agents in the first electrolyte and the second electrolyte can be the same or different. However, the difference is usually only partial, and the mass of the impedance reducing agent in the second electrolyte that is different from that in the first electrolyte is usually controlled within 20% of the total mass of the impedance reducing agent in the second electrolyte.
[0051] There is no specific restriction on the types of wetting improvers in the first electrolyte and the second electrolyte, such as at least one of fluorobenzene (FB), ethyl propionate, and propyl acetate, but it is not limited thereto. The types of wetting improvers in the first electrolyte and the second electrolyte can be the same or different. However, the difference is usually only partial, and the mass of the wetting improver in the second electrolyte that is different from that in the first electrolyte is usually controlled within 20% of the total mass of the wetting improver in the second electrolyte.
[0052] There is no specific restriction on the types of negative electrode SEI film improvers in the first electrolyte and the second electrolyte, such as both can include at least one of ethylene sulfite (ES), 1,4-butane sultone, propylene sulfite, dimethyl sulfite, diethyl sulfite, etc., but it is not limited to this. The types of impedance reducers in the first electrolyte and the second electrolyte can be the same or different. However, the difference is usually only partial, and the mass of the negative electrode SEI film improver in the second electrolyte that is different from that in the first electrolyte is usually controlled within 20% of the total mass of the negative electrode SEI film improver in the second electrolyte (such as 20%, 15%, 10%, 5%, 1%, 0.5% or the range formed by any two of the above values).
[0053] The additives in the first electrolyte and the second electrolyte may only include the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent, or may contain other additives, such as the positive electrode film forming additive, the flame retardant additive and the like.
[0054] Optionally, the mass fraction of the positive electrode film-forming additive in the first electrolyte is 0.2% to 1.0%, such as 0.2%, 0.4%, 0.6%, 0.8%, 1.0% or a range formed by any two of the above values. As an example, the positive electrode film-forming additive in the first electrolyte includes at least one of tripropargyl phosphate (TPP), ethylene sulfate, etc.
[0055] Optionally, the mass fraction of the positive electrode film-forming additive in the second electrolyte is 0.2% to 1.0%, such as 0.2%, 0.4%, 0.6%, 0.8%, 1.0% or a range formed by any two of the above values. As an example, the positive electrode film-forming additive in the second electrolyte includes at least one of tripropargyl phosphate (TPP), ethylene sulfate, etc.
[0056] There is no specific restriction on the types of lithium salts in the first electrolyte and the second electrolyte, such as lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium dioxalate borate, lithium difluorooxalate borate, lithium difluorodioxalate phosphate, lithium perchlorate, lithium difluorophosphate, but not limited thereto. Preferably, the lithium salts in the first electrolyte and the second electrolyte both include lithium hexafluorophosphate. Compared with other lithium salts, lithium hexafluorophosphate not only has good electrochemical properties, but also has low price and better comprehensive performance.
[0057] The types of lithium salts in the first electrolyte and the second electrolyte may be the same or different. However, the difference is usually only partial, and the mass of the lithium salt in the second electrolyte that is different from that in the first electrolyte is usually controlled within 20% of the total mass of the lithium salt in the second electrolyte (such as 20%, 15%, 10%, 5%, 1%, 0.5% or a range formed by any two of the above values).
[0058] In some embodiments, the method for preparing the first electrolyte includes the following steps: mixing and dispersing all its components to obtain the first electrolyte.
[0059] In some embodiments, the preparation method of the second electrolyte includes the following steps: mixing and dispersing all its components to obtain the second electrolyte.
[0060] In some embodiments, the active material of the positive electrode includes at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, wherein in the lithium nickel cobalt manganese oxide, the molar amount of nickel element / the total molar amount of nickel element, cobalt element and manganese element is ≥0.8, such as the ratio is 0.80, 0.82, 0.85, 0.88, 0.90, 0.92, 0.95, 0.98, 1.0 or a range value formed by any two of the above values; in the lithium nickel cobalt aluminum oxide, the molar amount of nickel element / the total molar amount of nickel element, cobalt element and aluminum element is ≥0.8, such as the ratio is 0.80, 0.82, 0.85, 0.88, 0.90, 0.92, 0.95, 0.98, 1.0 or a range value formed by any two of the above values. At this time, the active material of the positive electrode includes high-nickel ternary material with high energy density. By controlling the mass fractions of lithium salt and low-viscosity solvent in the second electrolyte to be higher than their mass fractions in the first electrolyte, and the sum of the mass fractions of impedance reducer, wettability improver and negative electrode SEI film improver in the second electrolyte to be higher than the sum of their mass fractions in the first electrolyte, the low-temperature discharge performance of the lithium-ion battery can be improved without losing the high energy density of the high-nickel ternary material, and its low-temperature capacity retention rate and discharge voltage can be increased.
[0061] According to the second aspect of the present application, a method for preparing the above-mentioned lithium-ion battery is provided, comprising the following steps: injecting the dried dry battery cell with a first electrolyte for the first time, infiltrating, forming, and aging, injecting the dried dry battery cell with a second electrolyte for the second time, returning helium to insert nails, welding sealing sheets, and dividing the capacity to obtain a lithium-ion battery.
[0062] According to the third aspect of the present application, an electrical device is provided, comprising the lithium ion battery or the lithium ion battery prepared by the preparation method. The selection of the electrical device is not specifically limited, such as electric vehicles, electronic devices, etc., but not limited thereto.
[0063] The present application is further described below through specific embodiments.
[0064] Examples 1 to 19 and Comparative Examples 1 to 6
[0065] Examples 1 to 19 and Comparative Examples 1 to 6 all provide a lithium ion battery, which includes a positive electrode, a negative electrode, a separator and an electrolyte, wherein the separator is disposed between the positive electrode and the negative electrode, and the electrolyte is infiltrated in the positive electrode, the negative electrode and the separator;
[0066] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on both sides of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material; the positive electrode active material is a high-nickel ternary material, specifically LiNi 0.88 Co 0.05 Mn 0.07 O2;
[0067] The negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on both sides of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material; the negative electrode active material is 450mAh / g silicon carbon, i.e., includes graphite and silicon material, wherein the silicon material is silicon oxide, and the mass fraction of the silicon material in the negative electrode active material is 7.9%;
[0068] The diaphragms all include a PE base film and a mixed coating of ceramic and PVDF (polyvinylidene fluoride) disposed on both sides of the base film;
[0069] The electrolytes include a first electrolyte and a second electrolyte. The compositions of the first electrolyte and the second electrolyte in each embodiment and comparative example are shown in Table 1. The preparation methods of the first electrolyte and the second electrolyte are as follows: LiPF6, LiPO2F2, FB, ES, PC, EMC, TPP, EC, DEC and FEC are mixed and dispersed to obtain the corresponding electrolytes.
[0070] These lithium-ion battery preparation methods include the following steps: stacking a positive electrode, a separator and a negative electrode in sequence to assemble a battery cell, drying, injecting a first electrolyte for the first time, high-temperature wetting, forming, aging, injecting a second electrolyte for the second time, returning helium to nail, welding a sealing sheet, dividing the capacity, and obtaining a corresponding lithium-ion battery, wherein the amount of the first electrolyte added (i.e., the mass fraction of the first electrolyte in the total electrolyte) and the amount of the second electrolyte added (i.e., the mass fraction of the second electrolyte in the total electrolyte) are shown in Table 1.
[0071] Table 1
[0072]
[0073]
[0074] Table 2
[0075]
[0076]
[0077] Effect example
[0078] The blue power test system was used to perform -20℃ 0.2C discharge test (2.5~4.25V@0.02C) and discharge average voltage test on the lithium ion batteries of each embodiment and comparative example. Before the test, the battery needs to be left at -20℃ or 25℃ for 4h. The -20℃ 0.2C discharge capacity retention rate calculation formula is as follows:
[0079] -20°C 0.2C discharge capacity retention rate = -20°C 0.2C discharge capacity / 25°C 0.2C discharge capacity × 100%.
[0080] See Table 3 for specific test data.
[0081] Table 3
[0082]
[0083]
[0084] It can be seen from Table 3 that the lithium-ion batteries of various embodiments have relatively high cycle capacity retention rate and average discharge voltage at -20°C, wherein the -20°C 0.2C discharge capacity retention rate is above 62.1%, and the -20°C 0.2C discharge average voltage is above 2.36V.
[0085] Compared with the comparison example 1 in which the mass fraction of the low viscosity solvent in the second electrolyte is the same as the mass fraction of the low viscosity solvent in the first electrolyte, the comparison example 2 in which the mass fraction of the low viscosity solvent in the second electrolyte is less than the mass fraction of the low viscosity solvent in the first electrolyte, the comparison example 3 in which the mass fraction of the lithium salt in the second electrolyte is the same as the mass fraction of the lithium salt in the first electrolyte, the comparison example 4 in which the mass fraction of the lithium salt in the second electrolyte is less than the mass fraction of the lithium salt in the first electrolyte, the sum of the mass fractions of the impedance reducing agent, the wetting improving agent and the negative electrode SEI film improving agent in the second electrolyte and the sum of the mass fractions of the impedance reducing agent, the wetting improving agent and the negative electrode SEI film improving agent in the first electrolyte For the same comparative example 5 and comparative example 6 in which the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the second electrolyte is less than the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the first electrolyte, Example 3 has a significantly higher cycle capacity retention rate and discharge average voltage at -20°C because the mass fractions of the lithium salt and the low-viscosity solvent in the second electrolyte are controlled to be higher than their mass fractions in the first electrolyte, respectively, and the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the second electrolyte is higher than the sum of their mass fractions in the first electrolyte.
[0086] By comparing Examples 1 to 4, it can be seen that the ratio of the mass fraction of the low viscosity solvent in the first electrolyte and the second electrolyte / the mass fraction of the silicon material in the negative electrode active material will affect the low-temperature performance of the battery. When the mass fraction of the low viscosity solvent in the first electrolyte / the mass fraction of the silicon material in the negative electrode active material is in the range of 4.2 to 4.7 and the mass fraction of the low viscosity solvent in the second electrolyte / the mass fraction of the silicon material in the negative electrode active material is in the range of 4.9 to 5.4, the battery has a significantly higher cycle capacity retention rate and discharge average voltage at -20°C.
[0087] By comparing Example 3 with Examples 5 to 7, it can be seen that the mass fraction of the lithium salt in the first electrolyte and the second electrolyte will affect the low-temperature performance of the battery. When the mass fraction of the lithium salt in the first electrolyte is in the range of 11% to 15% and the mass fraction of the lithium salt in the second electrolyte is in the range of 12% to 17%, the battery has a significantly higher cycle capacity retention rate and average discharge voltage at -20°C.
[0088] By comparing Example 3 with Examples 8 to 12, it can be seen that the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the first electrolyte and the second electrolyte will affect the low-temperature performance of the battery. When the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the first electrolyte is in the range of 1.5% to 4.0% and the sum of the mass fractions of the impedance reducing agent, the wetting improver and the negative electrode SEI film improver in the second electrolyte is in the range of 2.0% to 5.0%, it has a significantly higher cycle capacity retention rate and discharge average voltage at -20°C.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lithium ion battery, characterized in that: comprising an electrolyte, wherein the electrolyte comprises a first electrolyte and a second electrolyte; The first electrolyte and the second electrolyte both include a lithium salt, a resistance reducing agent, a wettability improving agent, a negative electrode SEI film improving agent and a low-viscosity solvent, wherein the low-viscosity solvent in the first electrolyte and the second electrolyte has a viscosity at 25° C. lower than 2.5 mPa·S and a dielectric constant greater than 2.5; The mass fractions of the lithium salt and the low-viscosity solvent in the second electrolyte are respectively higher than their mass fractions in the first electrolyte; The sum of the mass fractions of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent in the second electrolyte is higher than the sum of their mass fractions in the first electrolyte; The lithium-ion battery further includes a negative electrode active material, and the negative electrode active material includes a silicon material; in the first electrolyte, the mass fraction of the low viscosity solvent / the mass fraction of the silicon material in the negative electrode active material is 4.2-4.7, the mass fraction of the lithium salt is 11%-15%, and the sum of the mass fractions of the impedance reducing agent, the wetting improving agent and the negative electrode SEI film improving agent is 1.5%-4.0%; in the second electrolyte, the mass fraction of the low viscosity solvent / the mass fraction of the silicon material in the negative electrode active material is 4.9-5.4, the mass fraction of the lithium salt is 12%-17%, and the sum of the mass fractions of the impedance reducing agent, the wetting improving agent and the negative electrode SEI film improving agent is 2.0%-5.0%; The mass fraction of the first electrolyte in the electrolyte is 45% to 85%, and the mass fraction of the second electrolyte in the electrolyte is 15% to 55%; In the first electrolyte and the second electrolyte, the mass fractions of the impedance reducing agent, the wettability improving agent and the negative electrode SEI film improving agent are all 0.5% to 3%.
2. The lithium-ion battery according to claim 1, characterized in that The silicon material includes at least one of silicon monoxide, silicon alloy, and silicon composite material.
3. The lithium ion battery according to any one of claims 1 to 2, characterized in that: The mass fraction of the impedance reducing agent in the second electrolyte is not lower than the mass fraction of the impedance reducing agent in the first electrolyte.
4. The lithium ion battery according to any one of claims 1 to 2, characterized in that: The mass fraction of the wettability improving agent in the second electrolyte is not lower than the mass fraction of the wettability improving agent in the first electrolyte.
5. The lithium ion battery according to any one of claims 1 to 2, characterized in that: The mass fraction of the negative electrode SEI film improver in the second electrolyte is not lower than the mass fraction of the negative electrode SEI film improver in the first electrolyte.
6. The lithium ion battery according to any one of claims 1 to 2, characterized in that: The low-viscosity solvents in the first electrolyte and the second electrolyte both include propylene carbonate and ethyl methyl carbonate; in the first electrolyte, the mass fraction of propylene carbonate is 5% to 10%, and the mass fraction of ethyl methyl carbonate is 15% to 35%; in the second electrolyte, the mass fraction of propylene carbonate is 10% to 15%, and the mass fraction of ethyl methyl carbonate is 20% to 40%.
7. The lithium ion battery according to any one of claims 1 to 2, characterized in that: At least one of the following conditions is met: (1) The impedance reducing agent in the first electrolyte and the second electrolyte includes at least one of lithium difluorophosphate, lithium difluorooxyphosphate, tris(trimethylsilyl)phosphate, and tris(trimethylsilyl)borate; (2) The wetting improving agent in the first electrolyte and the second electrolyte both includes at least one of fluorobenzene, ethyl propionate, and propyl acetate; (3) The negative electrode SEI film improver in the first electrolyte and the second electrolyte includes at least one of vinyl sulfite, 1,4-butane sultone, propylene sulfite, dimethyl sulfite, and diethyl sulfite; (4) The lithium salt in the first electrolyte and the second electrolyte includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium perchlorate, and lithium difluorophosphate; (5) The lithium-ion battery further comprises a positive electrode, the positive electrode comprising a positive electrode active material, the positive electrode active material comprising at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, wherein the molar amount of nickel element in the lithium nickel cobalt manganese oxide / the total molar amount of nickel element, cobalt element and manganese element is ≥ 0.8; and the molar amount of nickel element in the lithium nickel cobalt aluminum oxide / the total molar amount of nickel element, cobalt element and aluminum element is ≥ 0.
8.
8. A method for preparing a lithium ion battery according to any one of claims 1 to 7, comprising the following steps: The dried dry battery cell is injected with the first electrolyte for the first time, soaked, formed, aged, and then injected with the second electrolyte for the second time, and then helium is returned to the nail, the sealing sheet is welded, and the capacity is divided to obtain a lithium ion battery.
9. An electrical device, characterized in that: It comprises the lithium ion battery as claimed in any one of claims 1 to 7 or the lithium ion battery prepared by the preparation method as claimed in claim 8.